Caracterização dos foraminíferos bentônicos da plataforma continental de Pernambuco e da Paraíba, NE-Brasil - Bérgamo, Davy Barbosa (2019)
Foraminifera are Chromista of marine environments that can be used as an important instrument in oceanographic and paleoenvironmental studies, its distribution corroborates with greater knowledge of the characteristics of the continental shelves. According to this, the aim of this study was to analyze the distribution of benthic foraminiferous from the continental shelf of Pernambuco and Paraíba, correlating them to the abiotic and taphonomic aspects. The samples were collected at depths varying between 15 and 57m. In the laboratory, the standard protocol for Quaternary foraminiferous analysis was performed. The depth and distance of the coast showed influence on other abiotic factors and in the distribution of foraminifera. The assembly- Archaias angulatus, Textularia agglutinans, Amphistegina lessonii, Quinqueloculina lamarckiana and Peneroplis carinatus, was considered typical of the studied area, inhabiting warm, clear waters and of intense endosymbiotic relationship. In relation to the taphonomic analysis of the foraminiferous shells, there was a greater amount of unaltered shells. However, the altered shells were dominant in shallow areas up to ±22m, and above this depth, the unaltered shells presented higher rates. The origin of altered shells may be related to physicochemical factors of the environment and/or temporal factors, associated with relative variation of sea level along Quaternary.